2020
DOI: 10.1371/journal.pone.0231503
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing characterization of Slovenian carbapenem-resistant Klebsiella pneumoniae, including OXA-48 and NDM-1 producing outbreak isolates

Abstract: The first hospital outbreak of carbapenemase-producing Enterobacteriaceae in Slovenia occurred in 2014-2016. Whole genome sequencing was used to analyse the population of carbapenem-resistant Klebsiella pneumoniae collected in Slovenia in 2014-2017, including OXA-48 and/or NDM-1 producing strains from the outbreak. Methods A total of 32 K. pneumoniae isolates were analysed using short-read sequencing. Multilocus sequence typing and core genome multi-locus sequence typing were used to infer genetic relatedness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…No strains of these serotypes and sequence types were found in this study, but K54 ( wzi 66, wzi 115, n = 2) and K57 ( wzi 57, n = 1) were found, which may also be related to high virulence ( Zhong et al, 2020 ). The genetic diversity of K. pneumoniae is very rich and its serotypes and sequence types are not in a one-to-one correspondence, which is similar to previous studies ( Benulič et al, 2020 ; Lepuschitz et al, 2020 ). Many studies confirmed that the occurrence of K. pneumoniae is related to the environment of farms and K. pneumoniae can be spread through contaminated feed, feces, drinking water, and so on ( Wareth and Neubauer, 2021 ; Zhao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…No strains of these serotypes and sequence types were found in this study, but K54 ( wzi 66, wzi 115, n = 2) and K57 ( wzi 57, n = 1) were found, which may also be related to high virulence ( Zhong et al, 2020 ). The genetic diversity of K. pneumoniae is very rich and its serotypes and sequence types are not in a one-to-one correspondence, which is similar to previous studies ( Benulič et al, 2020 ; Lepuschitz et al, 2020 ). Many studies confirmed that the occurrence of K. pneumoniae is related to the environment of farms and K. pneumoniae can be spread through contaminated feed, feces, drinking water, and so on ( Wareth and Neubauer, 2021 ; Zhao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…The plasmid denoted as pEGY22_CTX-M-14 (GenBank accession ON261190) encoded, in addition to bla CTX-M-14b , aminoglycoside resistance genes (aph(6)-Id, aph(3 )-Ib, and aph(3 )-VIb), and the bla OXA-48 carbapenemase gene. IncL/M plasmids represent an emerging threat since they are currently identified to be a source of class D carbapenemase, bla OXA-48 , and responsible for the worldwide dissemination of bla CTX-M [39]. Isolate bearing such plasmid becomes resistant to all types of β-lactams and carbapenems [39], a situation that we encountered in the current study.…”
Section: Characterization Of Pegy22_ctx-m-14 and Its Similarity To In...mentioning
confidence: 68%
“…IncL/M plasmids represent an emerging threat since they are currently identified to be a source of class D carbapenemase, bla OXA-48 , and responsible for the worldwide dissemination of bla CTX-M [39]. Isolate bearing such plasmid becomes resistant to all types of β-lactams and carbapenems [39], a situation that we encountered in the current study. In silico analysis of the genetic context of bla CTX-M-14b revealed an upstream location of ISEcp1, one of the most detected IS elements in the genetic environment of the bla CTX-M-14 gene.…”
Section: Characterization Of Pegy22_ctx-m-14 and Its Similarity To In...mentioning
confidence: 68%
“…Our data indicated that all the nine IMP-4-producing K. pneumoniae strains belong to the same type, ST2253, which was different from the types previously reported. Carbapenemase IMP is often distributed among multiple STs in K. pneumoniae , especially some rare STs ( 13 ). The goeBURST algorithm ( http://www.phyloviz.net/ ) was used to infer the evolutionary relatedness of the STs.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid technological advances, whole genome sequencing (WGS) has emerged as a powerful tool for bacterial typing (13,14). The success in tracking worldwide epidemics (15)(16)(17)(18), regional outbreaks (16,19) and foodborne outbreaks (20,21) has demonstrated that the fine resolution of WGS can facilitate our understanding of how infectious agents spread.…”
Section: Introductionmentioning
confidence: 99%